Five comedies - Sand, George, 1804-1876 (SUNY series, women writers in translation., 2003)
"Best known as a novelist, George Sand (1804-1876) was also arguably the most successful woman dramatist in history. More than twenty of her plays were staged in major Paris theaters to widespread popular and critical acclaim. Translated here for the first time into English are her two most famous full-length comedies, The Marquis de Villemer and Francoise, as well as her three major one-act plays, The Paving Stone, The Japanese Lily, and A Good Deed Is Never Wasted. Noted for their lively characterization, sparkling dialogue, and deft constructions, her plays reflect the passion and generosity of her own character, as well as a quick-witted sense of humor." "The translations are preceded by an introduction outlining Sand's theatrical career, the main themes and characteristics of her plays, and critical appraisals from her own generation to the present day. The translations are followed by notes and a bibliography."--Jacket